(untitled) (Medicine Today, 2013)
There has been increasing the incidence of addiction to certain drugs amongst people belonging to various strata of society particularly amongst young people in our country as well as western countries. Our patient is a 24 year old male with a history of phensidyl addiction for 4.5 years. Without having it he cant do anything. If he cannot take it, peevish temperament occurs and he doesnt wish to work or even talk. He collects drugs from the local spots or a particular person. This condition is very much dangerous both to the individual and socio-economic condition of a country. Drugs addiction is a condition of periodic or chronic intoxication produced by the repeated consumption of a drug or drugs by and individual effect of which is detrimental to the individual or to the society. A more intensive research, action program, and social movement are needed. It is also needed to strengthen family and social values and religious ethics in order to maintain a stable and drug-free society. DOI: http://dx.doi.org/10.3329/medtoday.v24i2.15014 Medicine Today 2012 Vol.24(2): 82-84